Государственное регулирование закупок учебного оборудования и инфраструктуры в школах (Government Regulation in the Procurement of Teaching Facilities and Infrastructures in Schools) - Zaharah, Zaharah; Kirilova, Galia Ildusovna (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractEducational policy is the key to excellence, even a form of nation-state existence in global competition. Educational policy is understood as part of public policy in the field of education, aimed at achieving the development goals of the country and nation. While the facilities and infrastructure owned by schools are a supporting factor for the implementation of school programs, especially learning activities carried out by teachers. The purpose of this article is to analyze how the actual government regulations in terms of procurement of facilities and infrastructure in the field of education, because there are also many schools that are located in the regions or in the interior are very minimal with the infrastructure they have. This is due to the disobedience of the school principals or the head of the education office regarding the regulations of the local and central government so that they do not dare to submit the needs of the school, especially in terms of procurement of school facilities and infrastructure. Resulting in very minimal schools with the facilities and infrastructure needed. The method used in writing this article is a descriptive analysis method using literature data literature. The results and conclusions obtained state that government regulations in the provision of facilities and infrastructure in the field of education are listed in ministerial regulation number 24 of 2007 which states that the National Education Standards on Facilities and Infrastructure can optimize the procurement, distribution, inventory, maintenance, storage and elimination of facilities and educational infrastructure. Therefore, the role of government is needed to support the provision of facilities and infrastructure in schools or in educational institutions.Keywords: Government Regulation, Infrastructure Facilities Abstrak Kebijakan pendidikan merupakan kunci bagi keunggulan, bahkan merupakan wujud eksistensi negara-bangsa dalam persaingan global. Kebijakan pendidikan dipahami sebagai bagian dari kebijakan publik di bidang pendidikan, yang ditujukan untuk mencapai tujuan pembangunan negara dan bangsa. Sedang sarana dan prasarana yang dimiliki sekolah merupakan faktor pendukung terlaksananya program sekolah, khususnya kegiatan pembelajaran yang dilakukan oleh guru. Adapun tujuan dari artikel ini adalah untuk menganalisis bagaimana regulasi pemerintah sebenarnya dalam hal pengadaan sarana dan prasarana di bidang pendidikan, karena banyak juga terlihat sekolah- sekolah yang berada di daerah ataupun di pedalaman sangat minim dengan sarana prasarana yang mereka miliki. Hal ini disebabkan karena ketidaktauan para kepala sekolah ataupun kepala dinas pendidikan tentang regulasi pemerintah daerah dan pemerintah pusat sehingga mereka tidak berani untuk mengajukan keperluan sekolah khususnya dalam hal pengadaan sarana dan prasarana sekolah. Sehingga mengakibatkan sekolah-sekolah sangat minim dengan sarana dan prasarana yang dibutuhkan. Metode yang digunakan dalam penulisan artikel ini adalah metode deskriptif analisis dengan menggunakan literatur data kepustakaan. Hasil dan kesimpulan yang didapat menyatakan bahwa regulasi pemerintah dalam hal pengadaan sarana dan prasarana di bidang pendidikan tercantum dalam peraturan menteri nomor 24 Tahun 2007 yang menyatakan bahwa Standar Nasional Pendidikan tentang Sarana dan Prasarana dapat mengoptimalkan pengadaan, penyaluran, inventarisasi, pemeliharaan, penyimpanan dan penghapusan sarana dan prasarana pendidikan. Oleh karena itu, diperlukan peran pemerintah untuk mendukung pengadaan sarana dan prasarana di sekolah atau di lembaga pendidikan.Kata Kunci: Regulasi Pemerintah, Sarana Prasarana Аннотация Образовательная политика является ключом к совершенству, даже формой существования государства в глобальной конкуренции. Образовательная политика понимается как часть государственной политики в области образования, направленной на достижение целей развития нации и страны. Оборудование и инфраструктура, принадлежащие школам, являются вспомогательным фактором для реализации школьных программ, особенно учебных мероприятий, проводимых учителями. Целью данной статьи является анализ того, как исполняются фактические государственные нормативные акты в области обеспечения оборудованием и инфраструктурой в области образования, поскольку многие школы расположенные в отдаленных районах региона, имеют слабо развитую инфраструктуру. Это связано с невыполнением директорами школ или главами управления образования правил местного и федерального правительств, с тем чтобы они не осмелились представить потребности школы, особенно с точки зрения приобретения школьных помещений и инфраструктуры. В результате многие школы не имеют необходимого оборудования и инфраструктуры. Метод, используемый при написании этой статьи, представляет собой метод анализа на основе использования данных литературы. Полученные результаты и сделанные заключения показывают, что правительственные нормативные акты в области обеспечения оборудованием и инфраструктурой в области образования перечислены в министерском постановлении No 24 от 2007 года, в котором говорится, что Национальные образовательные стандарты оборудования и инфраструктуры могут оптимизировать закупки, распределение, инвентаризацию, техническое обслуживание, хранение и списание оборудование и образовательной инфраструктуры. Поэтому государство необходимо для поддержки обеспечения объектов и инфраструктуры в учебных заведениях школ.Ключевые слова: Государственное регулирование, инфраструктура, объекты